2003
DOI: 10.1242/jeb.00516
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the coordinate regulation of glycolytic enzyme genes by hypoxia

Abstract: SUMMARYTwo billion years of aerobic evolution have resulted in mammalian cells and tissues that are extremely oxygen-dependent. Exposure to oxygen tensions outside the relatively narrow physiological range results in cellular stress and toxicity. Consequently, hypoxia features prominently in many human diseases, particularly those associated with blood and vascular disorders,including all forms of anemia and ischemia. Bioenergetic enzymes have evolved both acute and chronic oxygen sensing mechanisms to buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
3
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 100 publications
6
110
3
6
Order By: Relevance
“…It has been suggested that glycolytic enzymes in a variety of organisms are coordinately upregulated during hypoxic stress (Webster, 2003). Our data do not support a simple interpretation of this hypothesis, which predicts increased levels of all glycolytic enzymes in a given tissue during hypoxia.…”
Section: Variation Within the Glycolytic Pathwaycontrasting
confidence: 99%
“…It has been suggested that glycolytic enzymes in a variety of organisms are coordinately upregulated during hypoxic stress (Webster, 2003). Our data do not support a simple interpretation of this hypothesis, which predicts increased levels of all glycolytic enzymes in a given tissue during hypoxia.…”
Section: Variation Within the Glycolytic Pathwaycontrasting
confidence: 99%
“…Since the activation of HIFs did not contribute to the detected upregulation of HCV replication at 3% O 2 , we examined global cellular gene expression changes in mock-and JFH1/adpt1-infected Huh7.5 cells using hypoxia signaling pathway-focused DNA microarrays. Cells cultured for 24 h at 3% O 2 showed (18,47) an upregulation (by at least 2-fold) of several hypoxia-related genes (see Table S2 in the supplemental material), such as HIFs, directing transcriptional targets (VEGFA, EPO), genes encoding stress-related proteins, and genes involved in oxidative stress and reactive oxygen species (ROS) production, glucose transport (GLUT1, GLUT8) and metabolism (HK2, ENO1), cell growth, proliferation, and cell cycle regulation, including the FOS, MYCN, and KIT oncogenes. Notably, the respective transcript levels in uninfected and infected cells were similar.…”
Section: Resultsmentioning
confidence: 99%
“…43 The expression of a number of hypoxia 'marker genes' is reliably increased or decreased in conditions leading to oxidative damage: hypoxia has been shown to trigger the phosphorylation of constitutively expressed hypoxia-inducible factors (HIFs) directly leading to an increased antioxidant response (to mop-up ROS) and altered expression of glycolytic and oxidative phosphorylation proteins. 44 Two hypoxia-inducible factors (HIF3a and HIF-1b) were significantly increased at the transcript level in the schizophrenia prefrontal cortex.…”
Section: Hypoxiamentioning
confidence: 99%